Enhancing Security, Economy, and Education: A Policy Analysis of the Indonesia-Malaysia Border Region - Putri Lili; Adie Dwiyanto Nurlukman; Amiludin Amiludin; Toddy Aditya (Universitas Negeri Semarang, 2024)
This study explores the legal and policy dimensions influencing security, economic development, and education in the Indonesia-Malaysia border region, identifying key challenges and offering policy recommendations. Using a qualitative methodology and NVIVO 12+ software for data analysis, the research examines legislation documents, government reports, and policy frameworks to uncover significant gaps. The study reveals critical deficiencies, including underfunded educational institutions, inadequate healthcare facilities, and insufficient infrastructure, which hinder both human development and economic growth. For instance, many border villages face infrastructural deficits such as unpaved roads and unreliable electricity, limiting access to education and curbing local economic opportunities. The research also highlights the fragmentation of legal and policy frameworks, which often prioritize national security and macroeconomic goals over local needs, exacerbating socio-economic inequalities. Inadequate security measures further undermine regional stability, facilitating transnational crimes such as human trafficking and illegal trade. The study emphasizes the interconnectedness of education, infrastructure, security, and economic development, underscoring how deficiencies in one area adversely affect the others. This paper offers novel insights into border governance, proposing an integrated policy approach that aligns legal, economic, and educational objectives to foster sustainable development, enhance security, and promote regional cooperation. The findings provide valuable implications for policymakers seeking to improve governance in border regions facing similar socio-political challenges.